Cambios identitarios de los jóvenes indígenas de Cotopaxi :Estudio de caso en las comunidades de "San Isidro" y "Maca Grande" - Muñoz Naranjo, Duval Ricardo (2015)
We hope that this work will serve as a complement to the various works that have been written on this subject. As also can be used as a reference for the academy. At the same time we want to contribute to a better understanding of the cultural changes that are occurring in our reality. The structure of this research is divided into five chapters ; in the first two chapters the problem of identity change arises also envision the techniques that are focused on the ethnographic method , which allowed acquired information and interpret it from its social context. In chapter three geographical situation, shwthe cultural and socioeconomic situation of the two communities represent. The chapter four made comparison of cultural peculiarities between the circumstances in the previous generation and the current reality of the communities of San Isidro and Maca Grande. The present research prior to obtaining the degree of Bachelor of Intercultural Bilingües Education with specialization in Community Development, whose main objective view of identity changes in young indigenous communities of San Isidro and Maca Grande. Finally in chapter five findings the conclutones of the current realities facing our young people in society are made.